AN EXAMINATION OF THE XENOPHOBIC VIOLENCE IN SOUTH AFRICA AND ITS IMPACT ON SOCIO-ECONOMIC LIVES OF NIGERIANS IN THAT COUNTRY “2015-2019” - Nwobi, Uchechukwu Anthony; Nwokoma, Uchenna B; Uzozie, Harmony Adaku (African Journal of Social and Behavioural Sciences, 2020)
The paper was to examine the xenophobic violence and its impacts on socioeconomic lives of Nigerian workers in South Africa. This is because the persistent plague of xenophobic violence on Nigerians in South Africa increased drastically and affected Nigerian workers greatly despite a national outcry and crucial national discussions to mitigate it. Specifically, the study was to examine the impact of the xenophobic violence on homes, education, employments and basic needs of Nigerians in South Africa. Intergroup Threat theory was used as the theoretical umbrella. The study was qualitative. A secondary source of data was used. Content analysis was used to analyze data so generated. Findings revealed that the attacks made most Nigerians homeless and education wasn’t accessible. Others became unemployed and some could not meet their basic needs. The study recommended for the government to provide adequate housing support services for victims, ensure that Nigerians in South Africa are not denied access to education, device a means for Nigerians to make a living at home, create job via training on skills acquisition and improve basic needs through provision of food, health service, portable water etc.